Role of Micro-ESR and I/T Ratio in the Early Diagnosis of Neonatal Sepsis - Walliullah, ASM; Islam, MN; Siddika, M; Hossain, MA; Chowdhury, AK (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):56-61. The abstract of this article is available on the PubMed website